Wet carbonation potential of Mg- and Al-bearing calcium silicate clinker phases - Villmow, Sophia; Mielkau, Anika; Zajac, Maciej; Neubauer, Jürgen (Journal of CO2 Utilization, 2026)
In this study, the carbonation behavior of Ca-Mg/Al silicates was investigated in a specially designed wet reactor. The Mg/Al-rich phases studied represent a diverse group of materials, whose carbonation kinetics depend on their chemical composition and crystal structure. The reactions of synthetic akermanite (C2MS2), bredigite (C7MS4), merwinite (C3MS2), and gehlenite (C2AS) were monitored through continuous pH and temperature measurements, while data on the CO2 uptake, the dissolution and precipitation of hydrates, and carbonation products were measured by quantitative X-ray diffraction (QXRD) and thermogravimetric analysis (TGA). Under the given conditions, the Ca-Mg silicates exhibited a degree of reaction above 80 % within just three hours. In contrast, the Ca-Al silicate gehlenite showed little to no carbonation potential. Characteristic carbonation and hydration products include CaCO₃ (ACc, calcite, aragonite), (Ca,Mg)CO₃, and amorphous SiO2 gels.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Akermanite (C; Bredigite (C; Carbonation products; CO; Gehlenite (C; Merwinite (C; Reaction kinetics; Thermal analysis; X-ray diffraction